Characterization of a novel virus associated with the MVX disease of Agaricus bisporus - Maffettone, Eliana (Cranfield University, 2007)
‘Mushroom Virus X’ (MVX) disease of the cultivated mushroom Agaricus bisporus first arose in UK during the 1990’s. This disease resulted in devastating crop losses in the UK and gradually became more widespread (e.g. Netherlands and Eire). Up to twenty-six, non-encapsidated, double stranded RNA (dsRNA) elements have been found to be associated with diseased mushrooms, and these are believed to be the result of a complex of viruses. Although considerable data has accumulated on the symptoms of infection, aetiological sources, epidemiology and molecular characterization of the MVX dsRNA elements are limited. Research described in this thesis focused principally on sequence characterization of a frequently occurring dsRNA element ( MVX 14.4), which was shown to be a novel Endornavirus. Assigned ‘Agaricus bisporus endornavirus 1’ (AbEV1), this represents the first endornavirus known to infect edible mushrooms. AbEV1 is the first MVX element to be fully sequenced. Putative domains for RNA-dependent RNA polymerase (RdRp), helicase and glycosyltransferase were identified and used in comparisons with other viruses. Characterization of an AbEV1- type dsRNA found in a culture sample derived from a wild Agaricus bisporus collection indicates a possible source of the MVX dsRNA infections. Epidemiological studies were used to demonstrate that the AbEV1 dsRNA was transmissible both vertically through spores and horizontally by mycelial anastomosis between infected donor and MVX free acceptor strains. As a first step in the effort to understand the role of AbEV1in MVX infections and to investigate possible host defence mechanisms, dsRNA hairpin sequences were introduced into A. bisporus by Agrobacterium-mediated transformation. Both helicase and RdRp sequences were able to confer resistance to the uptake of MVX dsRNA elements in transformants. These observations suggest that homology-dependent gene silencing pathway(s) may be present in A. bisporus and represent a residual antiviral defence mechanism. Advances and approaches developed in this project open new opportunities to characterize the other dsRNA elements from the MVX complex, to further our understanding of mycovirus infections and host responses, and to investigate the origins of infectious dsRNA elements.